Epidemiology of acute diarrhea by rotavirus, Lara State, January 2015-July 2016 (Revista Venezolana de Salud Pública, 2019)
Acute diarrhea caused by rotavirus has become a public health problem that can affect the psychomotor and pondoestatural development of infants. This paper aims to determine the epidemiology of acute diarrhea caused by rotavirus in Barquisimeto, Lara State, in the period January 2015-July 2016. This research has a quantitative, field, experimental, descriptive and transversal nature. Prior informed consent, the data was collected in a protocol developed for this purpose. Samples (240) were collected at the "Agustin Zubillaga" University Pediatric Hospital in Barquisimeto, Lara State. They were subjected to a direct ELISA. The results were analyzed with the Microsoft Excel 2010 program. rotavirus was detected in (20%) of the samples. Rotavirus predominated in the female gender (62%) and in young infants (60%), followed by older infants (25%). The most frequent signs and symptoms were fever (95%), vomiting (95%) and rhinorrhea (85%). In relation to the associated diseases, anemia (60%), malnutrition (48%) and parasites (45%) were reported. Regarding the vaccine coverage against rotavirus, it was determined that (86%) of the rotavirus positive patients had not received any dose of said vaccine, while (14%) of said patients had received some doses of it.
Keywords: Epedemiology; diarrhea; rotavirus; ELISA